Board attributes and bank performance in light of Saudi corporate governance regulations - Omer Saeed Habtoor (Journal of Risk and Financial Management, 2022)
This study investigates the relationship between various attributes of boards of directors on bank performance in light of Saudi corporate governance regulations. The data set of this study is extracted from the annual reports of all 12 banks listed on the Saudi Stock Exchange (Tadawul) over a period of 10 years from 2009 to 2018. To test the study hypotheses, check the robustness of the results, and address potential endogeneity issues, this study applies different statistical methods, including FGLS, OLS, RE, PLCSE, and 2SLS, using STATA version 17. The results of multivariate analysis show that board size has a significant positive influence only on operational bank performance (ROA). For board composition, the results show that while board independence has a significant negative impact on accounting-based performance (ROA and ROE), it affects positively and significantly the market-based performance (Tobin's Q). Regarding board education, the results indicate that board members with at least a Bachelor's degree have a significant negative impact on ROA and ROE. In contrast, PhD holders on the board have a significant positive impact on ROA and ROE, while Master's holders affect positively and significantly all measures of bank performance. With respect to board diversity, only the CEO nationality has a significant positive effect on ROA and ROE. Board IT experience is found to be significantly and positively associated with ROA and ROE, while board meeting attendance has a significant positive influence only on ROE. These findings have important implications, especially for Saudi regulatory authorities to assess the current practice and compliance with the Saudi corporate governance regulations (SCGRs) and the principles of corporate governance for banks operating in Saudi Arabia (PCGB) regarding board characteristics and provide insights to improve board effectiveness and corporate governance practice in general.
Keywords: G3; G21; L25; O16; 650; corporate governance; board education; board diversity; board IT experience; Saudi Arabia